(untitled) (Rheumatology Reports, 2011)
The use of anti-tumour necrosis factor alpha (anti-TNFα) therapies has increased over the past few years. Concerns have been raised about the theoretical increased risk of malignancy in patients receiving these therapies. We report a case of an extremely rare high grade pleural based sarcoma in a patient with rheumatoid arthritis and a 7-year history of anti-TNFα therapy.